Economic optimization of microgrids based on peak shaving and CO2 reduction effect: A case study in Japan. (25th October 2021) - Zhang, Liting; Yang, Yongwen; Li, Qifen; Gao, Weijun; Qian, Fanyue; Song, Lifei
Abstract: Microgrids are an attractive way to deal with energy depletion and environmental deterioration as well as grid pressure. However, the energy configurations of microgrids comprising various uncertain and variable resources are significantly sophisticated. Focusing on the peak shaving ability and carbon reduction effect of microgrids, this paper proposes a multi-criteria evaluation method that aims to maximize the comprehensive value of microgrids. To unify these criteria with different perspectives when solving the optimization problem, the peak shaving and emission reduction effects are converted into economies through peak load cost and carbon tax rather than using the weighting method. The results of a case study in Higashida, Japan obviously evidenced the superiority of multi-objective optimization. Although the improvement of the peak shaving ability and emission reduction effect was partially at the expense of system cost benefit, the total cost under multi-criteria was still reduced by 2.13%, which indicates that the balance and optimization of the economic benefit, peak shaving and carbon reduction were realized. The effect of each evaluation criterion on the optimal configuration was analyzed by comparing the optimization results under objective functions with different criteria combinations. High requirements for carbon reduction can promote the development of renewable energy, and peak shaving ability should be ensured by controllable and stable power generators. Highlights: Analyze the characteristics of grid load for five multi-types buildings in Japan. Propose evaluation criteria including, economic, peak shaving and CO2 emission. Introducing peak load price and CO2 tax, evaluation criteria are converted into cost. The configuration of microgrid is optimized quantitatively under multi-evaluation. Effect of each criterion is carried out by comparing different criteria combinations.